BRAC Education Program (BEP) NFPE phase III (1999-2004) Review 1999-2000 - Ryan, Anne; Smith, Brigid (© BRAC, 2016)
1. Provision of the full primary cycle rather than just three grades 2. A slight change in the balance of girls and boys enrolled and an increased emphasis on life skills training for adolescents 3. Creation of an in-house unit for developing pedagogical and evaluative capacity 4. Significant operational changes through a decentralisation of quality management to field level.